Evolutionary history of continental Southeast Asians: “Early Train” hypothesis based on genetic analysis of mitochondrial and autosomal DNA data - Abdulla, Mahmood Ameen; Jinam, T.A.; Lih, C.H.; Phipps, M.E.; Stoneking, M.; Edo, J.; Saitou, N. (Oxford University Press, 2012)
The population history of the indigenous populations in island Southeast Asia is generally accepted to have been shaped by two major migrations: the ancient “Out of Africa” migration ~50,000 years before present (YBP) and the relatively recent “Out of Taiwan” expansion of Austronesian agriculturalists approximately 5,000 YBP. The Negritos are believed to have originated from the ancient migration, whereas the majority of island Southeast Asians are associated with the Austronesian expansion. We determined 86 mitochondrial DNA (mtDNA) complete genome sequences in four indigenous Malaysian populations, together with a reanalysis of published autosomal single-nucleotide polymorphism (SNP) data of Southeast Asians to test the plausibility and impact of those migration models. The three Austronesian groups (Bidayuh, Selatar, and Temuan) showed high frequencies of mtDNA haplogroups, which originated from the Asian mainland ~30,000–10,000 YBP, but low frequencies of “Out of Taiwan” markers. Principal component analysis and phylogenetic analysis using autosomal SNP data indicate a dichotomy between continental and island Austronesian groups. We argue that both the mtDNA and autosomal data suggest an “Early Train” migration originating from Indochina or South China around the late-Pleistocene to early-Holocene period, which predates, but may not necessarily exclude, the Austronesian expansion.